Community Service Lecture: The Role of Packaging in Increasing Marketing of Micro, Small and Medium Enterprises (MSMEs) Products Wilna Familly Cibatu Village, Cikembar District, Sukabumi Regency - Adhhawiyah, Elsya Rahmatul; Aziz, Abdul; Jamilah, Siti; Alawiyah, Tuti; Nurhajah, Nurhajah; Ichsan, Rully Moch (Indonesian Journal of Society Development, 2024)
Abstract: This community service activity aims to improve marketing and product development for Micro, Small and Medium Enterprises( MSMEs) in Cibatu Village. The implementation of Community Service activities is carried out using lecture, guidance and dialogue methods. Based on the results of observations and sampling interviews with participants, it can be concluded that the implementation of PKM provides additional knowledge for participants regarding packaging to support the development of MSME businesses, not only that, MSME players also gain basic knowledge about labels as information about the products being marketed. This PKM also emphasizes the importance of presenting products in an attractive manner. It is hoped that this will actually help get more attention from potential consumers when they see the packaging of the product being offered. In the packaging of a product, the packaging can be small or large according to the type of product. Marketers consider packaging issues to be the 5th aspect after the "4P" price, place, product, promotion. This means proving how important the role of packaging is in marketing industrial products